Evaluasi Kualitas Pelayanan Halte SMPN 5 Karawang di Kabupaten Karawang - Ekthy Putri Anggraini; Riyan Suganda; Hasna Nurhanifah; R. Caesario Boing Rachmat Raharjo (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
A bus stop (halte) is one of the essential supporting facilities for public transportation and plays a critical role in sustaining community mobility, particularly among students, in areas experiencing high mobility pressure such as Karawang Regency, an area widely recognized as a major industrial zone in West Java. One example of such a facility is the SMPN 5 Karawang bus stop, which functions as a primary access point for students, educators, and surrounding residents. This study aims to evaluate the service quality of the SMPN 5 Karawang bus stop by assessing the suitability of its existing physical facilities against the Minimum Service Standard (Standar Pelayanan Minimum/SPM) established under Decree of the Directorate General of Land Transportation Number 271/HK.105/DRJD/96, and to identify which service attributes require priority improvement. A descriptive qualitative and quantitative approach was employed, combining direct field observation, standardized facility inventory forms, systematic photographic documentation, and interviews with users and bus stop managers, complemented by secondary data obtained from relevant regional agencies. Facility fulfillment levels were calculated using a percentage-based compliance formula applied separately to mandatory (primary) and supplementary facility categories. The results indicate that of the ten facility items assessed, only the identity signage was available, albeit in a deteriorated condition, while the protective canopy was present but structurally unfit for use; the remaining eight items, including seating, route information boards, and lighting, were entirely absent. The overall compliance rate reached only 10 percent, with primary facilities at 16.7 percent and supplementary facilities at 0 percent, indicating that the bus stop has not yet met minimum service expectations and requires facility rehabilitation as the top improvement priority. This study is expected to inform local government policy for improving bus stop infrastructure and student transportation safety.